2012
DOI: 10.1371/journal.pone.0033805
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Is More Effective than Cromolyn in Blocking Human Mast Cell Cytokine Release and Inhibits Contact Dermatitis and Photosensitivity in Humans

Abstract: Mast cells are immune cells critical in the pathogenesis of allergic, but also inflammatory and autoimmune diseases through release of many pro-inflammatory cytokines such as IL-8 and TNF. Contact dermatitis and photosensitivity are skin conditions that involve non-immune triggers such as substance P (SP), and do not respond to conventional treatment. Inhibition of mast cell cytokine release could be effective therapy for such diseases. Unfortunately, disodium cromoglycate (cromolyn), the only compound markete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 82 publications
(91 reference statements)
5
117
0
1
Order By: Relevance
“…[40][41][42] However, it has also been reported that dietary quercetin did not reduce NF-κB expression/activation in the renal cortex of rats, 43) which suggests that flavonoids may act in an organspecific manner. A more thorough understanding of the effects of dietary quercetin will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] However, it has also been reported that dietary quercetin did not reduce NF-κB expression/activation in the renal cortex of rats, 43) which suggests that flavonoids may act in an organspecific manner. A more thorough understanding of the effects of dietary quercetin will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…They both inhibit the release of histamine, leukotrienes, and prostaglandin D 2 from human cultured MCs in response to cross-linkage of Fc«RI (Kimata et al, 2000). Quercetin also inhibits histamine, IL-6, IL-8, TNF-a, and tryptase release from human MCs Park et al, 2008), as well as asthma in a guinea pig model (Moon et al, 2008) and contact dermatitis in humans (Weng et al, 2012). Luteolin has also been reported to inhibit stimulation of activated T cells (Kempuraj et al, 2008), keratinocytes (Weng et al, 2014a), and microglia (Jang et al, 2008).…”
Section: Il-33 In Autoimmune and Inflammatory Disordersmentioning
confidence: 99%
“…It has been identified potent mast cells stabilizer effect of natural components (flavonoids, phenols, terpenoids, coumarins) [4,5]. Furthermore considerable non-gastrointestinal symptoms are typical for IBS as well.…”
Section: Reasons Of Hemorrhoidmentioning
confidence: 99%
“…Particularly, flavonoids express mast cells stabilizer effect, exactly among them are quercetin, rutin, fisetin, kaempferol. Furthermore quercetin decreases IL-1b, IL-6, IL-8 and TNF production and more effectively inhibits cytokines release from human mast cells, than mast cells well known stabilizer cromolyn [4][5][6][7].…”
Section: Reasons Of Hemorrhoidmentioning
confidence: 99%